ANALISIS KELAYAKAN FINANSIAL PENGOPERASIAN ANGKUTAN ANTAR JEMPUT SISWA SEKOLAH PADA KORIDOR JALAN GUNUNG AGUNG DENPASAR - Nyoman Sriastuti, D. A.; Putu Suparsa, I G.; Priyantha Wedagama, D. M. (JURNAL SPEKTRAN; Vol 1, No 1, Januari 2013, 2013)
The population increase in Denpasar City causes the increase of peoples’ activities which is followed by the increase of using transportation facilities. It certainly influences the traffic in the city itself. One of the peoples’ activities causing traffic jams on the streets of Denpasar particularly on Gunung Agung Street is the students’ pick-up service. The jam is mainly caused by the use of private vehicles especially motorcycles for picking-up the students. The problem can be overcome with pick up service so that the use of private vehicles can be minimized. Some advantages can be gained from the pick-up service; it can be done door to door in accordance with the students’ schedules and it can help the parents who are in troubles in bringing and picking-up their children to schools. A planning and an evaluation on aspects of financial investment feasibility towards the students’ pick-up service are needed in order to match both the interests of service providers and the customers. This research used field survey method completed with interview method. The interview method was applied to gain primary data from related parties and from related institutions for the secondary data. Tariff calculation analysis based on the vehicle operational cost (VOC) used a method of Transportation Department, and the Ability to Pay (ATP) tariff and Willing to Pay (WTF) tariff were determined based on respondents’ income and their perceptions toward a tariff they expected. The result of the research shows that the ATP tariff for both routes is higher than WTF tariff; on route I the ATP is Rp. 569,76 per kilometer-  passenger (Rp. 4,273 per passenger) and the WTP tariff is Rp. 499,67 per kilometer-passenger (Rp. 3,748 per passenger), on route II the ATP tariff is Rp. 594,46 per kilometer-passenger (Rp. 3,864 per passenger) and the WTP tarrif is Rp. 554,56 per kilometer-passenger (Rp. 3,605 per passenger). Based on the estimation of the passengers, there are 97 vehicles estimated for route I and 38 for route II. Based on the tariff analysis, it can be recommended that tariff based on VOC + 15% margins is Rp. 797,47 per kilometer-passenger (Rp. 5,981 per passenger) for route I and Rp. 1,645,08 per kilometer-passanger (Rp. 10,693 per passenger) for route II. The financial evaluation analysis shows that the three criteria such as Net Future Value, Benefit Cost ration, and Internal Rate of Return for route I and route II are not feasible to be operated if they are operated both by personal and corporation agents.
Keywords: Transportation Analysis, Financial Analysis